Frequency of arylsulphatase A pseudodeficiency associated mutations in a healthy population. Issue 9 (September 1994) - Barth, M L; Ward, C; Harris, A; Saad, A; Fensom, A
Abstract : Arylsulphatase A (ASA, EC 3.1.6.1) is a lysosomal enzyme that catalyses cerebroside sulphate degradation. ASA deficiency is associated with metachromatic leucodystrophy (MLD), a rare autosomal recessive disorder, which is characterised by the storage of cerebroside sulphate. Low ASA activities can be also observed in clinically healthy persons, a condition termed ASA pseudodeficiency. Two mutations responsible for the majority of pseudodeficiency alleles have been defined in the ASA gene. These are both A-->G transitions. One causes an asparagine to serine substitution (N350S). The second changes the first polyadenylation signal downstream of the stop codon (1524 + 95A-->G), which causes a severe deficiency of one ASA mRNA species. The incidence of the pseudodeficiency allele is estimated to be high in the general population and can be found in families carrying MLD associated mutations. We report a reliable stratagem for detecting the two PD associated mutations separately, which we have applied to a healthy population. Two homozygotes for the N350S and 1524 + 95A-->G mutations were detected, which gives a population frequency of 2.6%. The overall frequencies of the ASA-PD mutations were shown to be 17.5% for the N350S change and 13.0% for the 1524 + 95A-->G change, estimating each mutation separately. In addition, the frequency of both PD associated mutations occurring together on the same chromosome was found to be 12.3% in our population. The study has also allowed us to establish a new control ASA activity range, which was based on assay of blood from persons who had been shown at the DNA level not to carry ASA PD associated mutations.